Autophagy and Reactive Oxygen Species Are Involved in Neutrophil Extracellular Traps Release Induced by C. albicans Morphotypes - Kenno, Samyr; Perito, Stefano; Mosci, Paolo; Vecchiarelli, Anna; Monari, Claudia (Frontiers in Microbiology, 2016)
Neutrophil extracellular traps (NETs) are a combination of DNA fibers and granular enzymes, such as elastase and myeloperoxidase. In this study we demonstrate that C. albicans hyphal (CAH) cells and yeast (CAY) cells induce differential amounts, kinetics and mechanisms of NET release. CAH cells induced larger quantities of NET compared to CAY cells and can stimulate rapid NET formation up to 4 h of incubation. CAY cells are, also, able to induce rapid NET formation, but this ability was lost at 4 h. Both reactive oxygen species (ROS) and autophagy are implicated in NET induced by CAH and CAY cells, but with a time-different participation of these two mechanisms. In particular, in the early phase (15 min) CAH cells stimulate NET via autophagy, but not via ROS, while CAY cells induce NET via both autophagy and ROS. At 4 h, only CAH cells stimulate NET formation using autophagy as well as ROS. Finally we demonstrate that NET release, in response to CAH cells, involves NF-kB activation and is strongly implicated in hyphal destruction.